安樂死: 一種儒家倫理之考量: Euthanasia: A Confucian Ethical Approach - LI, Jun (International Journal of Chinese & Comparative Philosophy of Medicine, 2009)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文從儒家倫理的視角對安樂死問題加以考量。本文指出，由於儒家對於死後生活的淡漠，使得其更接近世俗倫理的思路，從而可以與安樂死的支持者對話。儒家培養忍耐痛苦的弘毅德性，從而不鼓勵通過選擇死亡來解除痛苦；通過對倫理關係構成人本質的洞察，更反對生死自主的迷誤，指出倫理關係的相關者必須為此負責。但是安樂死對於生命尊嚴的追求在儒家思想上是值得尊重的，關鍵在於這種追求能否鞏固人們生活在其中的倫理關係。 This essay reexamines the issue of euthanasia from the perspective of Confucian ethics. The author, as a Confucian scholar, responds to and analyzes the ethical challenge posed by euthanasia. In this way, the essay constitutes a preliminary attempt to establish a Confucian understanding of and attitude towards euthanasia. Confucians generally see death as the end of life in this world, leaving open the question of the immortality of the soul or the resurrection of the body. This view differs little from that generally held in the secularized modern world and seems close to a pro-euthanasia position, making Confucianism different from any other great ancient tradition. On the philosophical level, however, Confucianism views a meaningful life as the process of becoming a saint or sage, which entails the cultivation of important virtues, including endurance and strength. In this sense, attempting to seek death as a means of escaping suffering is not encouraged, however neither is it viewed as evil, for Confucians do not have such an absolute transcendental standard as the Christian Decalogue to prohibit suicide. Rather, for Confucians, the moral sense of an action can only be determined through the context of ethical relations. Hence, it is necessary to rethink euthanasia in the sociopolitical dimension of Confucianism. For Confucians, ethical relationships constitute not only communities and societies but also humanity. In this sense, it is essentially wrong to advocate the autonomy of individuals because to do so ignores the relational network in which and by which decisions emerge on the individual level. Confucianism stresses the dependence of individuals upon the ethical network such that people are responsible for their family members’ and friends’ “own” decisions. Euthanasia, then, cannot be reduced to suicide because it contains the element of homicide. Nevertheless, Confucianism supports respect for human dignity, which is a pro-euthanasia argument. In the Confucian tradition, it is vitally important to ensure the dignity of dying people, not only for their own comfort but also for the consolidation of their ethical relationships, in which they have experienced love and care and which will last long after their death. For Confucians, what is at stake in the issue of euthanasia is whether it can consolidate the ethical relational network on which dying people depend, and whether thereafter a meaningful death can shaped for the patient. DOWNLOAD HISTORY | This article has been downloaded 3861 times in Digital Commons before migrating into this platform.